2015
DOI: 10.1007/s10008-015-2942-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of V2O5·1.6H2O/graphene composite and its application in supercapacitors

Abstract: V 2 O 5 ·nH 2 O/graphene composite is synthesized by self-assembly of V 2 O 5 ·1.6H 2 O nanobelts on the surface of graphene via a simple hydrothermal method. The structure and morphologies of the composites are characterized by thermogravimetry analyzer, x-ray diffraction, and scanning electron microscope, respectively. It's found that the V 2 O 5 · 1.6H 2 O nanobelts are in width of 90 nm and length of 1.5 μm. The electrochemical behaviors of the composites in supercapacitors are tested by cyclic voltammetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Comparing 1), the specific capacitance of 8 % YbÀ V 2 O 5 • nH 2 O thin film electrode is much higher. [38][39][40][41][42][43][44][45][46][47] The above phenomenon is consistent with the CV results, which proves that doping proper amount of Yb 3 + can improve markedly electrochemical performance of V 2 O 5 • nH 2 O. Figure 4d shows the GCD test results of 8 % YbÀ V 2 O 5 • nH 2 O thin film electrode under different current densities ranging from 0.5 A g À 1 to 5 A g À 1 .…”
Section: Resultssupporting
confidence: 78%
“…Comparing 1), the specific capacitance of 8 % YbÀ V 2 O 5 • nH 2 O thin film electrode is much higher. [38][39][40][41][42][43][44][45][46][47] The above phenomenon is consistent with the CV results, which proves that doping proper amount of Yb 3 + can improve markedly electrochemical performance of V 2 O 5 • nH 2 O. Figure 4d shows the GCD test results of 8 % YbÀ V 2 O 5 • nH 2 O thin film electrode under different current densities ranging from 0.5 A g À 1 to 5 A g À 1 .…”
Section: Resultssupporting
confidence: 78%
“…To further improve the material charge storing capabilities, Geng et al. synthesized V 2 O 5 ⋅ 1.6H 2 O nanobelts/graphene composites by self‐assembly‐hydrothermal technique . They found that the V 2 O 5 ⋅ 1.6H 2 O nanobelts were typically ∼90 nm in width and ∼1.5 μm long.…”
Section: V2o5‐carbon‐based Compositesmentioning
confidence: 99%
“…Similar diffraction patterns have also been observed in chemically pre-intercalated δ-V 2 O 5 . [29][30][31][32][33] Essentially, these compounds originate from the parent material of…”
mentioning
confidence: 99%